A comprehensive assessment of plastic remediation technologies. (March 2023) - Leone, Giulia; Moulaert, Ine; Devriese, Lisa I.; Sandra, Matthias; Pauwels, Ine; Goethals, Peter L.M.; Everaert, Gert; Catarino, Ana I.
Graphical abstract: Highlights: Plastic remediation technologies include clean-up and prevention systems. Lack of knowledge on the environmental impact of plastic remediation technologies. Most plastic remediation technologies target inland waterways. Plastic remediation technologies minimize the amount of plastic in the environment. Plastic clean-up technologies offer crucial opportunities such as data collection. Abstract: The global presence of plastic litter and its accumulation in the environment has become an issue of concern to the public and policymakers. This concern has triggered innovators in past decades to design and develop a multitude of remediation technologies to prevent plastic from entering the environment, or to clean up legacy litter. This study aims to (i) systematically review the current scientific literature on plastic remediation technologies, (ii) create a 'plastic clean-up and prevention overview' illustrating 124 remediation technologies and 29 characteristics, (iii) qualitatively analyse their key characteristics (e.g., fields of application, targeted plastic), and (iv) investigate challenges and opportunities of clean-up technologies for inland waterways (e.g., canals, rivers) and ports. We identified 61 scientific publications on plastic remediation technologies, until June 2022. Thirty-four of these studies were published within the last three years, demonstrating a growing interest. The presented overview indicates that inland waterways are, so far, the preferred field of application, with 22 technologies specifically designed for cleaning up plastics from inland waterways, and 52 additional ones with the potential to be installed in these locations. Given the importance of clean-up technologies in inland waterways, we highlighted their strengths, weaknesses, opportunities, and threats (SWOT). Our results indicate that, despite the challenges, these technologies provide essential prospects, from improving the environmental quality to raising awareness. Our study is instrumental as it illustrates an up-to-date overview and provides a comprehensive analysis of current in design phase, testing, and in use plastic remediation technologies.